KABA GOMBANG PATUANAN DALAM PANDANGAN POSKOLONIAL - Eva Krisna (Widyariset, 2010)
Kaba Gombang Patuanan in the view of colonialism. This research discusses the representation of nativeresistance againts colonialism through life rature. This research used observation method and interpretation-understanding(verstehen-hermeneutic). In an occidental discourse, the superiority prominent of the colonized peopleto show that the colonizer is not the center of power.